THE EFFECTIVENESS OF BLENDED LEARNING MODEL IN TEACHING WRITING NARRATIVE TEXT TO THE ELEVENTH GRADE STUDENTS AT SMA NEGERI 5 MODEL LUBUKLINGGAU - Triananda, Rialisa; Ramasari, Maria; Syafitri, Dewi (ELite Journal : International Journal of Education, Language and Literature, 2023)
The purpose of this research was to find out the empirical evidence of the student's effectiveness in writing narrative text by using WhatsApp in the Blended Learning model on students' writing abilities. This research used a Pre-Experimental method. The sample in this research was 34 students (XI MIPA 1) taken by cluster sampling. The pre-experimental class has given the treatments using WhatsApp in Blended Learning, Pre-test was given before giving treatments. The result showed as follows: first, the pre-test score showed that the average score was 44.73. After being given treatments, a post-test was given. The post-test result showed that the average score was 84.35. Second, the sample score of the independent T-test shows the significant value (2-tailed) is 5.41 1.693. In other words, (Ho) was rejected and (Ha) was accepted. In short, it can be announced that students who write narrative text using WhatsApp in the Blended Learning model are effective. So, it can be concluded that WhatsApp in Blended Learning was effective to the eleventh-grade students at SMA N 5 Model Lubuklinggau in academic year 2022/2023.